2016
DOI: 10.3390/e18040134
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement and Entropy Generation of Nanofluids Laminar Convection in Microchannels with Flow Control Devices

Abstract: Abstract:The heat transfer enhancement and entropy generation of Al 2 O 3 -water nanofluids laminar convective flow in the microchannels with flow control devices (cylinder, rectangle, protrusion, and v-groove) were investigated in this research. The effects of the geometrical structure of the microchannel, nanofluids concentration ϕ(0%-3%), and Reynolds number Re (50-300) were comparatively studied by means of performance parameters, as well as the limiting streamlines and temperature contours on the modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…In the forced conductive flow with heat transfer, the entropy generation contains two parts, one caused by the heat transfer irreversibility, and the other due to the fluid frictional irreversibility [22]. The entropy generation of flow can be calculated by the following equations [23] …”
Section: Parameter Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the forced conductive flow with heat transfer, the entropy generation contains two parts, one caused by the heat transfer irreversibility, and the other due to the fluid frictional irreversibility [22]. The entropy generation of flow can be calculated by the following equations [23] …”
Section: Parameter Definitionmentioning
confidence: 99%
“…As for the internal microchannel flow, the entropy generating rate per unit length is calculated by [23] …”
Section: Parameter Definitionmentioning
confidence: 99%
“…After the pioneering works by Choi [16], Eastman et al [17], Eastman et al [18], Xuan and Li [3], and Choi et al [19], nanofluids have been extensively studied experimentally, theoretically and numerically [20][21][22][23][24][25][26][27][28]. In a recent review by Lomascolo et al [29], it has been shown that the number of annual journal publications about nanofluids has been growing exponentially.…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic mixture model has been widely used by many researchers to study nanofluid heat transfer with low-particle concentration as it provides reasonably accurate results with less computing power and time [21][22][23][24]32,37,38]. Thus, the macroscopic model is the best suited for the present study.…”
Section: Introductionmentioning
confidence: 99%